Supply chain performance flexibility in the Australian beef industry. Issue 4 (3rd July 2016) - Jie, Ferry; Parton, Kevin A.; Mustafid,
Abstract : The red meat value chain in Australia is undergoing a rapid change due to globalisation, a highly competitive meat market and increased production efficiency and flexibility. This paper aims to investigate how beef producers can increase supply chain performance (SCP) flexibility by improving supply chain practices. A model was developed and hypotheses were formulated based on the literature review of agri-food supply chains. A survey questionnaire was distributed to beef producers in Australia and the results of stepwise multiple regression analysis revealed that performance flexibility was significantly influenced by the supply chain practices: customer relationships and information quality (IQ). Given these findings, beef producers should focus on customer relationships and IQ in order to achieve enhanced flexibility in their SCP. The paper discusses the implications and current practices in beef cattle farming industry.